Vendor Rating Using Analytical Hierarchical Process - Insights from Indian Engineering Construction Industry - Haridasan, Vani; M, Sudharsan (International Journal of Scientific Research and Management (IJSRM), 2018)
Vendor Evaluation and Selection is one of the most critical activities of purchasing management in supply chain. It is a complex problem involving qualitative and quantitative multi-criteria. A trade-off between these tangible and intangible factors is essential in selecting the best supplier. This paper aims to develop a vendor rating system for Engineering Construction Industry where there is a huge involvement in the purchases of Pipes (like Ductile Iron, Mild Steel, HDPE, RCC, PVC), Pumps, Electrical items (like Panels, PLC, Motors, Generators) and Mechanical items for Water & Effluent Treatment Projects. The conventional method is less accurate in ranking the vendors as a result of greater amount of subjectivity.This paper focuses on developing a Vendor Rating System using AHP methodology to choose the best suppliers in such a way to reduce the time taken for the selection process.